Case Report: Area of focus clinical presentation and KMT2D gene mutation at the c.15535C>T site in a case of Kabuki syndrome - Li, Wen; Lin, Mengjie; Dao, Jinwei; Shi, Li; Yi, Wei; Lei, Jia; Song, Yaxian; Dong, Jiaolou; Zhao, Meiwei; Xu, Yushan; Chen, Lulu (Frontiers in Genetics, 2025)
BackgroundKabuki syndrome (KS) is a rare autosomal dominant genetic disorder. The full understanding of KS remains elusive due to the heterogeneity of gene mutations, clinical phenotypes, and the associations and mechanisms linking genotypes to phenotypes. This study reports on a 16-year-old male patient diagnosed with type I Kabuki syndrome following the identification of a de novo mutation, c.15535C>T (p.Arg5179Cys), in the KMT2D gene.Case ReportA 16-year-old male presented with bilateral breast enlargement persisting for over 1 month. Historically, the patient exhibited intellectual disability. Both parents are healthy with no similar family history. The patient’s father had a history of heroin use for 8 years prior to the patient’s birth. On examination, the patient had unclear speech and slow speech rate, with diminished reading comprehension and calculation abilities. Characteristic facial features of KS were noted. Breast development was observed (Tanner stage II on the right and III on the left), with pain upon deep palpation of the left nipple. Molecular genetic testing identified a heterozygous missense mutation, c.15535C>T (p.Arg5179Cys), in theKMT2Dgene, confirming the diagnosis of type I Kabuki syndrome.DiscussionKS is characterized by distinctive facial features: arched eyebrows, eversion of the eyelids, long palpebral fissures, a short nasal septum, a flat nasal tip, auricular deformities, a small mandible, a high palatal arch, or cleft palate. The patient exhibited a heterozygous missense mutation in the coding region of the KMT2D gene, identified as a de novo mutation. Currently, KS management primarily involves symptomatic and rehabilitative therapies.